Stages of human development - Mansilla A., María Eugenia (2000)
In this article it is presented the discussion of the concept of the human development and their different stages in whose formulation has been considered the variable age, atmosphere, problems as well as the psychological consequences in the human beings; the theoretical base; the carried out analysis; the consulted bibliographic and of some of the carried out investigations, published and unpublished of the author; and, the proposal Stages of the Human Development."